Indicadores de insensibilização em tilápia-do-Nilo - Carlos, Clarissa Lerois [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The reduction of suffering at the time of production of animal slaughter is current concern, given the high production of Nile tilapia (Oreochromis nilocticus), monitoring the degree of pre-slaughter in fish stunning needs more study when compared to other species. And slaughter the most critical stage of breeding, the application of good management practices that meet the animal welfare becomes essential for success at this stage. Given the importance of exploring methods to unveil the fish level of consciousness at the time of stunning, this study aimed to test whether the bristling reflection of the dorsal fin (REN) produced by manual stimulation may be a candidate for sensitivity loss indicator . To this end, we explore, initially, the effects of benzocaine on reflection, anesthetic widely used for fish. Latency, duration and REN recovery rate was observed. We then apply stunning methods commonly used in fish farming, they are: termonarcose narcosis and carbon dioxide, in order to test whether the REN disappears as observed with benzocaine. In addition, we tested the reflection of eye rotation (RO) for the purpose of comparison between the REN and RO methods and the ability to correct posture during induction. All fish lost reflections analyzed at one point of the experiments, so our results show that the REN insensitivity can be indicator in the Nile tilapia. However, although the RO have more rapid loss and slower recovery than REN, there was little difference in time. So for RO and REN are reflexes are important to indicate stunning, and then it is possible to combine the two methods as a strategy for assessing unconsciousness in Nile tilapia

A redução do sofrimento no momento do abate de animais de produção é preocupação atual e, dada a alta produção de tilápia-do-Nilo (Oreochromis nilocticus), o monitoramento do grau de insensibilização pré-abate em peixes necessita mais estudos quando comparado a outras espécies. Sendo o abate a etapa mais crítica da criação animal, a aplicação de boas práticas de manejo que atendam o bem-estar animal torna-se essencial para obter êxito nesta fase. Diante da relevância de explorar métodos que desvendem o nível de insensibilização de peixes no momento da insensibilização, o presente estudo teve como objetivo testar se o reflexo de eriçamento da nadadeira dorsal (REN) produzido pelo estímulo manual pode ser candidato a indicador da perda de sensibilidade. Para tanto, exploramos, inicialmente, os efeitos da benzocaína sobre o reflexo, anestésico amplamente empregado para peixes. Foi observada a latência, duração e velocidade de recuperação do REN. Em seguida, aplicamos métodos de insensibilização comumente utilizados na piscicultura. São eles: termonarcose e narcose por dióxido de carbono, com a finalidade de testar se o REN desaparece como o observado com a benzocaína. Além disso, testamos o reflexo de rotação ocular (RO) com o objetivo de comparação entre os métodos REN e RO e a capacidade de corrigir a postura durante a indução anestésica. Todos os peixes perderam os reflexos analisados em dado momento dos experimentos, logo, nossos resultados mostram que o REN pode ser indicador de insensibilidade em tilápia-do-Nilo. Apesar de a RO ter perda mais rápida e recuperação mais lenta do que REN, houve pouca diferença de tempo. No entanto, por RO e REN serem reflexos, são importantes para indicar insensibilização, sendo possível unir os dois métodos como estratégia para aferir inconsciência em tilápia-do-Nilo
Keywords: Peixe; Tilápia-do-Nilo; Saude animal; Reflexos; Analise de sensibilidade; Fishes